Arabidopsis thaliana POLYOL/MONOSACCHARIDE TRANSPORTERS 1 and 2: fructose and xylitol/H+ symporters in pollen and young xylem cells. - Klepek, Yvonne; Volke, Melanie; Konrad, Kai R.; Wippel, Kathrin; Hoth, Stefan; Hedrich, Rainer; Sauer, Norbert (Journal of Experimental Botany, 2010)
The genome of Arabidopsis thaliana contains six genes, AtPMT1 to AtPMT6 (Arabidopsis thaliana POLYOL/MONOSACCHARIDE TRANSPORTER 1-6), which form a distinct subfamily within the large family of more than 50 monosaccharide transporter-like (MST-like) genes. So far, only AtPMT5 [formerly named AtPLT5 (At3g18830)] has been characterized and was shown to be a plasma membrane-localized H(+)-symporter with broad substrate specificity. The characterization of AtPMT1 (At2g16120) and AtPMT2 (At2g16130), two other, almost identical, members of this transporter subfamily, are presented here. Expression of the AtPMT1 and AtPMT2 cDNAs in baker's yeast (Saccharomyces cerevisiae) revealed that these proteins catalyse the energy-dependent, high-capacity transport of fructose and xylitol, and the transport of several other compounds with lower rates. Expression of their cRNAs in Xenopus laevis oocytes showed that both proteins are voltage-dependent and catalyse the symport of their substrates with protons. Fusions of AtPMT1 or AtPMT2 with the green fluorescent protein (GFP) localized to Arabidopsis plasma membranes. Analyses of reporter genes performed with AtPMT1 or AtPMT2 promoter sequences showed expression in mature (AtPMT2) or germinating (AtPMT1) pollen grains, as well as in growing pollen tubes, hydathodes, and young xylem cells (both genes). The expression was confirmed with an anti-AtPMT1/AtPMT2 antiserum (alphaAtPMT1/2) raised against peptides conserved in AtPMT1 and AtPMT2. The physiological roles of the proteins are discussed and related to plant cell wall modifications.